Characterization and expression profiling of PIN auxin efflux transporters reveal their role in developmental and abiotic stress conditions in rice - Manna, Mrinalini; Rengasamy, Balakrishnan; Ambasht, Navin Kumar; Sinha, Alok Krishna (Frontiers in Plant Science, 2022)
The auxin efflux transporter proteins called PINs, ferry auxin from its source to sinks in particular directions depending on their polar localizations in the plasma membrane thus facilitating development of the entire plant architecture. Rice genome has twelve PIN genes, distributed over eight chromosomes. To study their roles in plant development, abiotic stress responsiveness and shaping auxin dependent root architecture, genome wide analysis was carried out. Based on phylogeny, cellular localization and hydrophilic loop domain size, the PINs were categorized into canonical and noncanonical PINs. PINs were found to express in all the organs of plants which emphasized their indispensable role throughout the plant’s life cycle. We discovered that PIN5C and 9 were upregulated during salt and drought stress. We also found that irrespective of its cellular level, auxin functioned as a molecular switch to turn on auxin biosynthesis genes. On the contrary, though PIN expression was upregulated upon initial treatment of auxin, prolonged auxin treatment not only led to their downregulation, but also led to development of auxin dependent altered root formation in rice. Our study paves way for developing stress tolerant rice and plants with desirable root architecture by genetic engineering.